Bulgarian Icons in Wikidata and EDM - Alexiev, Vladimir; Tarkalanov, Plamen; Georgiev, Nikola; Pavlova, Lilia (Digital Presentation and Preservation of Cultural and Scientific Heritage, 2020)
We briefly describe Wikidata, its importance for GLAM institutions, iconographic authorities in Mix-n-Match. Then we propose an Icon KnowledgeGraph Model comprising the entities: iconographer, iconographic school, herminia, icon, measurements, material, technique, iconographic subject (saint or a title of the Virgin Mary), location (city, monastery, church, museum), scientific article, academic journal, issue, links to LOD datasets (e.g. VIAF, Getty AAT, ISBN, ISSN, academia.edu). Then we introduce the Virtual Encyclopedia of Bulgarian Icons (BIDL) and describe how we exported it to Wikidata, while coreferencing to iconographers, saints, locations; and the extra info we added for such entities. Finally, we describe a conversion to the Europeana Data Model, including details such as links to Wikidata, bilingual descriptions, language tags, providers. The online version of the paper includes live links; the accompanying presentation includes more images and queries.
Keywords: Knowledge Graphs; Semantic Integration; GLAM; Wikidata; Open- Refine; Icons; Religious Icons; Iconography; Iconographic Subject; CLADA; BIDL; Virtual Encyclopedia of Bulgarian Icons